Bond strength and internal adaptation of customized glass fiber posts using different bulk-fill flow resins - Fantin, Leticia-Lazzari (2022)
Background: this study aimed to evaluate the bond strength and internal adaptation of customized glass fiber posts using Bulk Fill flowable composite resins (BF) and conventional composite resin. Materials and Methods: Fifty bovine teeth were randomly divided (n=10) according to the following groups: G1 (control): glass fiber posts were adapted to the root canal and luted with Rely-X ARC cement (3M® ESPE); G2: fiber posts smaller than the root canal diameter were customized using Filtek™ Z350 XT (3M® ESPE) conventional composite resin, and luted similarly to Group 1. G3: posts were customized with Tetric N-Ceram Bulk Fill composite resin (Ivoclar Vivadent AG), G4: posts were customized with Filtek™ Bulk Fill Flow (3M® ESPE), and G5: posts were customized with SureFil SDRTM flow (DENTSPLY), respectively. The specimens were submitted to push-out testing and internal adaptation evaluation using optical microscopy. Push-out (MPa) and internal adaptation (%) data were subjected to ANOVA and Tukey’s post-hoc tests (p = 5%). Results: No statistically significant differences were found in both evaluations (p <0.05). Conclusions: Customized glass fiber posts using different bulk fill flowable composites did not affect the post bond-strength and internal adaptation, presenting similar results to customized glass fiber posts using conventional composite or posts with no previous customization.